1994
DOI: 10.1002/j.1460-2075.1994.tb06756.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin induces phosphorylation of Tyr694 of Stat5 (MGF), a prerequisite for DNA binding and induction of transcription.

Abstract: Mammary gland factor (MGF) is a transcription factor discovered initially in the mammary epithelial cells of lactating animals. It confers the lactogenic hormone response to the milk protein genes. We reported recently the isolation of the cDNA encoding MGF. MGF is a novel member of the cytokine‐regulated transcription factor gene family. Members of this gene family mediate interferon alpha/beta and interferon gamma induction of gene transcription, as well as the response to epidermal growth factor and interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
381
3
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 569 publications
(406 citation statements)
references
References 58 publications
21
381
3
1
Order By: Relevance
“…Treatment of T-47D cells with hPRL induces a rapid activation of STAT5b via phosphorylation of its Cterminal tyrosine (Gouilleux et al, 1994), which is time-(not shown) and dose-dependent (Figure 3a, left). As previously reported (Schaber et al, 1998), we failed to detect activation of Stat5a by PRL in T-47D (not shown).…”
Section: Stat5bmentioning
confidence: 93%
“…Treatment of T-47D cells with hPRL induces a rapid activation of STAT5b via phosphorylation of its Cterminal tyrosine (Gouilleux et al, 1994), which is time-(not shown) and dose-dependent (Figure 3a, left). As previously reported (Schaber et al, 1998), we failed to detect activation of Stat5a by PRL in T-47D (not shown).…”
Section: Stat5bmentioning
confidence: 93%
“…STAT5A is activated by and mediates the responses of many cell ligands, including IL2, IL3, IL7 GM-CSF, erythropoietin, thrombopoietin and various growth hormones. STAT5A was first identified as a PRL-induced mammary gland factor (Gouilleux et al, 1994) and has been demonstrated to play critical roles in regulating apoptosis, promoting proliferation and enhancing cell cycle progression (Paukku and Silvennoinen, 2004). This gene was previously reported to have effects on the milk protein percentage, the milk fat percentage and embryonic survival (Khatib et al, 2008).…”
Section: Association Analysis With Traditional Mcpsmentioning
confidence: 99%
“…One of them involves the activation of STAT proteins (Signal Transducer and Activator of transcription) by cytokine receptorassociated tyrosine kinases of the Jak family Ihle, 1996). The STAT proteins are latent cytoplasmic transcription factors that become tyrosine phosphorylated after ligand binding (Shuai et al, 1993;Gouilleux et al, 1994). Activated STATs dimerize (homo-or hetero-dimerize), migrate into the nucleus, bind to speci®c DNA elements and activate the transcription of responsive genes.…”
Section: Introductionmentioning
confidence: 99%